2020
DOI: 10.1128/mra.00652-20
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Arcanobacterium sp. Strain 2701, Isolated from a Harbor Seal

Abstract: Arcanobacterium spp. are Gram-positive bacteria which can be found in a wide range of hosts and can be associated with disease in humans and animals. Here, we announce the complete genome sequence of Arcanobacterium sp. strain 2701, isolated from a harbor seal from the North Sea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Sequencing procedures for strain 2701 T were already described by Borowiak et al . [15]. Briefly, genomic DNA was extracted after cultivation for 48 h at 37 °C under microaerobic conditions on sheep blood agar using the MagMAX Microbiome Ultra nucleic acid isolation kit (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequencing procedures for strain 2701 T were already described by Borowiak et al . [15]. Briefly, genomic DNA was extracted after cultivation for 48 h at 37 °C under microaerobic conditions on sheep blood agar using the MagMAX Microbiome Ultra nucleic acid isolation kit (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…The Whole Genome Shotgun project was deposited at DDBJ/ENA/GenBank under the accession number NZ_CP050804.1. The MinION and Illumina sequencing data were deposited in the NCBI Sequence Read Archive under the accession numbers SRX8129176 and SRX8130151, respectively [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In harbor seals and other marine mammals, Arcanobacterium phocae is widespread and sometimes associated with wound infections ( 6 , 7 ). Routine microbial diagnostic investigations performed as part of a program monitoring harbor seals in the German North Sea revealed that harbor seals also appear to be a natural reservoir for other Arcanobacterium species, as three novel species were identified—namely, Arcanobacterium phocisimile ( 8 , 9 ), A. buesumense ( 10 , 11 ), and A. pinnipediorum ( 1 , 12 ).…”
Section: Announcementmentioning
confidence: 99%